Kinetics of the Cellular and Transcriptomic Response to Eimeria maxima in Relatively Resistant and Susceptible Chicken Lines - Bremner, Abi; Kim, Sungwon; Morris, Katrina M.; Nolan, Matthew John; Borowska, Dominika; Wu, Zhiguang; Tomley, Fiona; Blake, Damer P.; Hawken, Rachel; Kaiser, Pete; Vervelde, Lonneke (Frontiers in Immunology, 2021)
Eimeria maxima is a common cause of coccidiosis in chickens, a disease which has a huge economic impact on poultry production. Knowledge of immunity to E. maxima and the specific mechanisms that contribute to differing levels of resistance observed between chicken breeds and between congenic lines derived from a single breed of chickens is required. This study aimed to define differences in the kinetics of the immune response of two inbred lines of White Leghorn chickens that exhibit differential resistance (line C.B12) or susceptibility (line 15I) to infection by E. maxima. Line C.B12 and 15I chickens were infected with E. maxima and transcriptome analysis of jejunal tissue was performed at 2, 4, 6 and 8 days post-infection (dpi). RNA-Seq analysis revealed differences in the rapidity and magnitude of cytokine transcription responses post-infection between the two lines. In particular, IFN-γ and IL-10 transcript expression increased in the jejunum earlier in line C.B12 (at 4 dpi) compared to line 15I (at 6 dpi). Line C.B12 chickens exhibited increases of IFNG and IL10 mRNA in the jejunum at 4 dpi, whereas in line 15I transcription was delayed but increased to a greater extent. RT-qPCR and ELISAs confirmed the results of the transcriptomic study. Higher serum IL-10 correlated strongly with higher E. maxima replication in line 15I compared to line C.B12 chickens. Overall, the findings suggest early induction of the IFN-γ and IL-10 responses, as well as immune-related genes including IL21 at 4 dpi identified by RNA-Seq, may be key to resistance to E. maxima.